(untitled) (Research, Society and Development, 2025)
The Internet of Bodies (IoB) represents the convergence between digital technologies and devices added to the body externally, internally or implanted, configuring a new frontier in health monitoring, diagnosis and interventions. The aim of this study is to analyze the foundations of the IoB, its current and future applications, the risks of cyber attacks associated with privacy and data security, and possible ethical dilemmas. The article is based on recent studies dealing with the implementation of body devices in clinical, wellness and biometric surveillance contexts. The results point to the need for a bioethical debate beyond regulations.